Copper plasmonic metamaterial glazing for directional thermal energy management. (March 2020) - Ma, Rui; Wu, Dong; Liu, Yumin; Ye, Han; Sutherland, Duncan
Abstract: In recent years, transparent solar technology has attracted increasing attention, which has the potential to let many of the surfaces of our buildings environment be turned into solar harvesting arrays without impacting their function or aesthetics. Glazing with nanostructured surface possessing different solar absorption ability from different directions is studied currently as a route to reduce the environmental cost of keeping appropriate indoor temperature. Here a transparent and solar thermal metasurface based on low cost copper plasmonic nanostructures is proposed and a maximum 25% difference in absorption from different sides is demonstrated experimentally. The spectra show strong activity in the infrared and still have transparency for visible light, which can be further improved by optimizing the structures according to the simulations. These materials are suitable as an alternative design of window glazing for energy saving. Graphical abstract: Unlabelled Image Highlights: A directional glazing effect of 25% was demonstrated with moderate transparency. A three times improved directional glazing was shown compared to previous studies. Copper, an abundant material, was used for window applications for the first time. Simulations gave good support for the understanding of principles of the design. Simulations predicted materials designs for even further improved color rendering.